1999
DOI: 10.1177/000331979905000701
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Thrombophlebitis of the Legs: A Randomized, Controlled, Follow-up Study

Abstract: The aim of the present study was to evaluate the effects of different treatment plans (compression only, early surgery, low-dose subcutaneous heparin [LDSH], low-molecular-weight heparin [LMWH], and oral anticoagulant [OC] treatment) in the management of superficial thrombophlebitis (STP), by considering efficacy and costs in a 6-month, randomized, follow-up trial. Patients with STP, with large varicose veins without any suspected/documented systemic disorder, were included. Criteria for inclusion were as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 5 publications
4
88
1
12
Order By: Relevance
“…[8][9][10][11][12][13][14] The few randomized studies that have been performed did not clarify the circumstances under which surgery is required or the value or optimal dose and duration of anticoagulant or antiinflammatory therapy. 6,[15][16][17][18][19] The results of the two largest studies, evaluating low-molecular-weight heparin, suggest that high-dose (therapeutic) or intermediate-dose regimens do not provide substantial benefits over low-dose (prophylactic) regimens and that a treatment period of 12 days or of 30 days is too short, with most symptomatic thromboembolic complications occurring after the treatment period. 6,17 None of the published studies showed a clinically relevant bene fit of any treatment as compared with placebo.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] The few randomized studies that have been performed did not clarify the circumstances under which surgery is required or the value or optimal dose and duration of anticoagulant or antiinflammatory therapy. 6,[15][16][17][18][19] The results of the two largest studies, evaluating low-molecular-weight heparin, suggest that high-dose (therapeutic) or intermediate-dose regimens do not provide substantial benefits over low-dose (prophylactic) regimens and that a treatment period of 12 days or of 30 days is too short, with most symptomatic thromboembolic complications occurring after the treatment period. 6,17 None of the published studies showed a clinically relevant bene fit of any treatment as compared with placebo.…”
Section: Resultsmentioning
confidence: 99%
“…1,[8][9][10][11][12] With one exception (case 12 with lung cancer), all patients in this study underwent surgery to prevent extension of the saphenous thrombus to a deep vein. Four cases underwent surgery after anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Belcaro et al, from an English and Italian group, conducted an RCT study to evaluate the effects of several STP management plans on progression of the STP and the incidence of concomitant DVT at 3-months follow-up. 16) They demonstrated that among several treatments: 1) ECS alone, 2) low dose subcutaneous heparin, 3) LMWH, 4) simple flush ligation of the saphenous vein, 5) stripping of affected veins, the incidence of STP extension was significantly higher in the group with 1) ECS, and 4) high ligation. They also showed that there was no significant difference in DVT incidence at 3-months follow-up among these treatment groups.…”
Section: Management Of Stp In the Varicose Veinsmentioning
confidence: 99%